Melatonin treatment combined with TGF-β silencing inhibits epithelialmesenchymal transition in CF41 canine mammary cancer cell line - Custódio, Paulo R.; Colombo, Jucimara; Ventura, Fabrício V.; Castro, Tialfi B.; Zuccari, Debora A. P. C. [UNESP] (Bentham Science Publishers, 2020)
Background: Mammary cancer is the most prevalent type of cancer in female dogs. The main cause of mortality is the occurrence of metastasis. The metastatic process is complex and involves the EpithelialMesenchymal Transition (EMT), which can be activated by Transforming Growth Factor beta (TGF-β) and involves changes in cellular phenotype, as well as, in the expression of proteins such as E-cadherin, N-cadherin, vimentin and claudin-7. Melatonin is a hormone with oncostatic and anti-metastatic properties and appears to participate in the TGF-β pathway. Thus, the present work aimed to evaluate the expression of EMT markers, E-cadherin, N-cadherin, vimentin and claudin-7, as well as, the cell migration of the canine mammary cancer cell line, CF41, after treatment with melatonin and TGF-β silencing. Methods: Canine mammary cancer cell line, CF41, was cultured and characterized in relation to markers ER, PR and HER2. Cell line CF41 with reducing expression level of TGF-βwas performed according to Leonel et al. (2017). Expression of the protein E-caderin, N-cadherin, vimentin and claudin-7 was evaluated by immunocytochemistry and quantified by optical densitometry. The analysis of cell migration was performed in transwell chambers with 8µM pore size membrane. Results: CF41 cells present a triple negative phenotype, which is an aggressive phenotype. Immunocytochemistry staining showed increased expression of E-caderin and claudin-7 (P˂0.05) and decreased expression of N-cadherin and vimentin (P˂0.05) in CF41 cells after treatment with 1mM melatonin and TGF-β silencing. Moreover, treatment with melatonin and TGF-β silencing was able to reduce migration in cell line CF41 (P˂0.05). Conclusion: Our data suggests that therapies combining TGF-β1 silencing and melatonin may be effective in suppressing the process of EMT, corroborating the hypothesis that melatonin acts on the TGF-β1 pathway and can reduce the metastatic potential of CF41 cells. This is so far the first study that reports melatonin treatment in CF41 cells with TGF-β1 silencing and its effect on EMT. Thus, further studies are needed to confirm this hypothesis.
Keywords: Canine mammary cancer; Epithelial Mesenchymal Transition (EMT); Melatonin; Metastasis; TGF-β; TGF-βsh